Antioxidant and Antiproliferative Effect of Pleurotus ostreatus - V.Kaviyarasan, D. Gunasundari, K. Radhika, R. Dandapani, Loganathan K. Jagadish, V. Venkatakrishnan, R. Shenbhagaraman, (Journal of Phytology, 2009)
In this study, ethanol extract of an edible mushroom Pleurotus ostreatus cultivated under the laboratory condition was investigated for its antioxidant and anticancer property in vitro. To confirm the total antioxidant activity, ABTS, DPPH free radical-scavenging assay was carried, along with total phenolic and flavonoid concentration. The ethanolic extract showed a potent antioxidant activity against both DPPH and ABTS radicals, with the EC50 value of 0.202±0.55 mg/mL and 6.42±0.261 mg/mL. Antioxidant components like total flavonoids were 1.82±0.15 µg/mg (Quercetin equivalent) and the total phenols were 8.52±0.6 mg/g (Catechin equivalent). Against the cancer cell (HL-60) in vitro P. ostreatus extracts exhibited the cytotoxic effect. The HL-60 cells treated with ethanol extract was further stained with propidium iodide and analyzed through flow cytometry, to identify whether the cytotoxicity induction was due to apoptosis or necrocis. The results of the flow cytometry confirm the cytotoxic effect of the mushroom extract was found to be mediated by the induction of apoptosis. In conclusion, our results supported the consumption of edible mushroom that act as a good dietary supplement and functional food.